Implantação de um condomínio sustentável - Campos, Victor Arruda Ferraz de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work presents ecotechnics applicable to civil construction for the use of rainwater harvesting, electric power generation from photovoltaic panels and sewage treatment. The objective of the work is the elaboration of the project of a residential condominium with focus on sustainability and energy efficiency. The condominium consists of ten houses that present pluvial water capture systems through the implantation of green roofs, which also function as thermal regulators and acoustic insulation. The system makes it possible to store rainwater for non-potable purposes in tanks buried in the soil. Integrated to the green roof, photovoltaic panels systems were designed for the microgeneration of electric energy needed to meet the monthly consumption of each residence, guaranteeing savings to the residents. The sewage collection network has been dimensioned in such a way that all residences receive sewage treatment in loco, with the installation of an ecological septic tank in the common area of the condominium. The feasibility of implementing these ecotechnics was verified by analyzing the installation costs and also the local climatic conditions. It was concluded that the ecotechnics presented are alternatives that integrate energy efficiency and sustainability, guaranteeing economy and environmental awareness

Neste trabalho são apresentadas ecotécnicas aplicáveis à construção civil para aproveitamento da água da chuva, geração de energia elétrica a partir de painéis fotovoltaicos e tratamento de esgoto. O objetivo do trabalho é a elaboração do projeto de um condomínio residencial com foco na sustentabilidade e eficiência energética. O condomínio é composto por dez casas que apresentam sistemas de captação de água pluvial através da implantação de telhados verdes, que também funcionam como reguladores térmicos e isolantes acústicos. O sistema possibilita o armazenamento da água da chuva para fins não potáveis em cisternas enterradas no solo. Integrados à cobertura verde, dimensionou-se sistemas de painéis fotovoltaicos para a microgeração de energia elétrica necessária para atender ao consumo mensal de cada residência, garantindo economia aos moradores. A rede coletora de esgoto foi dimensionada de tal forma que todas as residências recebem tratamento de esgoto in loco, com instalação de uma fossa séptica ecológica na área comum do condomínio. Verificou-se a viabilidade de implantação destas ecotécnicas a partir da análise dos custos de instalação e também das condições climáticas do local. Concluiu-se que as ecotécnicas apresentadas são alternativas que integram eficiência energética e sustentabilidade, garantindo economia e consciência ambiental
Keywords: Arquitetura sustentável; Eficiência do uso da água; Energia solar; Construção civil; Sustainable architecture